2012
DOI: 10.1111/j.1750-2659.2012.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

2009 pandemic Influenza A (H1N1): clinical and laboratory characteristics in pediatric and adult patients and in patients with pulmonary involvement

Abstract: Please cite this paper as: Lee and Liu et al. (2012) 2009 pandemic Influenza A (H1N1): clinical and laboratory characteristics in pediatric and adult patients and in patients with pulmonary involvement. Influenza and Other Respiratory Viruses 6(601), e152–e161. Background  To better understand clinical and laboratory characteristics in children, adults, and patients with lung involvement suffering 2009 pandemic influenza A (H1N1). Methods  A total of 442 patients with 2009 pandemic influenza A (H1N1) were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
15
2
Order By: Relevance
“…IA and COVID-19 are two infections sharing similar spectrums of symptoms. In addition, studies have shown that these symptoms occur in similar frequencies in adult IA and COVID-19 patients [3,5,10,13,14]. In this study of pediatric patients, however, COVID-19 caused fewer symptoms in spite of the exclusion of the asymptomatic cases.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…IA and COVID-19 are two infections sharing similar spectrums of symptoms. In addition, studies have shown that these symptoms occur in similar frequencies in adult IA and COVID-19 patients [3,5,10,13,14]. In this study of pediatric patients, however, COVID-19 caused fewer symptoms in spite of the exclusion of the asymptomatic cases.…”
Section: Discussioncontrasting
confidence: 46%
“…In uenza A (IA) virus and SARS-CoV-2 cause similar symptoms such as fever and cough, especially at the early stages of the disease. However, contrary to COVID-19, studies have shown that IA manifests more symptoms in children than in adult [5]. Therefore, it is necessary to study the symptomological disparities between the two diseases in pediatric patients.…”
Section: Read Full License Introductionmentioning
confidence: 88%
“…In addition, the serum levels of LDH increased in pneumocystis pneumonia (PcP) patients, probably was due to lung injury [ 13 , 14 ]. Among patients who were infected during the 2009 influenza A (H1N1) pandemic, 77.8% whose laboratory test showed LDH > 225U/L had lung involvement, without differences between adult and children [ 15 ], which indicated that LDH elevation was associated with various pathogens including viruses, and was relevant to lung injury. Furthermore, there was a case reported in 2017 that a patient with human Zika virus infection had markedly elevated LDH, which was associated with 70% mortality in further a Zika-infected animal study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [19] found that LDH can be recognized as an important predictive factor for severe COVID-19 manifestations. It must be emphasized that during the 2009 influenza A (H1N1) pandemic, 77.8% of patients whose laboratory data indicated elevation of LDH, had lung involvement, suggesting that LDH elevation was associated with multiple pathogenic factors including viruses, and was important to lung injury [20]. In addition, Henry et al [19] recently demonstrated that elevated LDH values were associated with the risk of developing severe disease (sixfold increase) and mortality (16-fold increase).…”
Section: Discussionmentioning
confidence: 99%